Penurunan Kadar COD, BOD dan Nitrit Limbah Pabrik Tahu Menggunakan Karbon Aktif Ampas Bubuk Kopi - Zulhaini Sartika; Mariana Mariana; M. Dani Supardan (Fakultas Teknik, 2019)
The industrial wastewater load pollutant caused without treatment. This study uses a simple technology to reduce the levels of COD, BOD5, and Nitrite by using coffee husk to minimized waters pollution or environmental damage. Adsorbents are activated by HCl 0.1 N and carbonized with muffle furnance to enlarge the surface area of the sorbent and to absorb the contaminants in the effluent of tofu industry. Tofu wastes containing COD, BOD5 and Nitrite contacted with activated carbon with varying weight of 0.2, 0.3, 0.4 gr and different stirring times 10, 20, 30, 40, 50, 60 minutes and 125 rpm stirring speed with biosorbent size 80-100 mesh. The stirring time 10-30 minutes with the average concentration absorbed for BOD5 180 mg/l, COD 650 mg/l and NO2- 20 mg/l and increasing the mass of biosorbent can increase the concentrasion of adsorption. The efficiency absorption of wastewater absorbs more BOD5 than COD and Nitrite with BOD5 absorption efficiency is 85.38%. Adsorption of BOD5, COD and Nitrite follows Langmuir’s isotherm equation with R2 value is 0,8104 for BOD5, 0,7121 for COD and 0,7467 for nitrite